Chemical Structures of Specific Sodium Ion Battery Components Determined by Operando Pair Distribution Function and X‐ray Diffraction Computed Tomography. Issue 38 (9th August 2017) - Sottmann, Jonas; Di Michiel, Marco; Fjellvåg, Helmer; Malavasi, Lorenzo; Margadonna, Serena; Vajeeston, Ponniah; Vaughan, Gavin B. M.; Wragg, David S.
Abstract: To improve lithium and sodium ion battery technology, it is imperative to understand how the properties of the different components are controlled by their chemical structures. Operando structural studies give us some of the most useful information for understanding how batteries work, but it remains difficult to separate out the contributions of the various components of a battery stack (e.g., electrodes, current collectors, electrolyte, and binders) and examine specific materials. We have used operando X‐ray diffraction computed tomography (XRD‐CT) to study specific components of an essentially unmodified working cell and extract detailed, space‐resolved structural information on both crystalline and amorphous phases that are present during cycling by Rietveld and pair distribution function (PDF) methods. We illustrate this method with the first detailed structural examination of the cycling of sodium in a phosphorus anode, revealing surprisingly different mechanisms for sodiation and desodiation in this promising, high‐capacity anode system. Abstract : Inside a battery : Operando X‐ray diffraction computed tomography was used to study specific components of an essentially unmodified working cell and extract structural information on crystalline and amorphous phases present during cycling by Rietveld and pair distribution function methods. This method was applied for the first detailed structural examination of the cycling of sodium in a phosphorus anode.